COORDINATION OF GOVERNMENT BODIES AND PUBLIC ASSOCIATIONS ACTIVITY IN MODERN UKRAINE - Hololobov S.M. (Pressing Problems of Public Administration, 2016)
In the article the objective necessity, social importance of coordination of government agencies andNGOs, principles, ways and means of achieving the agreed cooperation, the harmonious developmentof elements of the political system - the state, political parties, public organizations of Ukraine wereexplored.